THE IMPACT OF SMARTPHONE USAGE ON PRESCHOOL AND SCHOOL-AGE CHILDREN INTELLIGENCE - Utami, Titania Novira (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – The internet is very important and useful for a variety of purposes, such as rapid sharing of information, entertainment, convenient electronic commerce, emotional support, and contact with other cultures, in the end, the internet is what we need, and so we use smartphones. A smartphone combines a mobile phone and the services of the internet. Smartphones offer many useful services that relieve our daily lives. Smartphones are not only used by young adult people, but also commonly used by children, both those are preschool and school-age children. Children spend a lot of time using smartphones instead of playing with their friends in real life. Some of them are even addicted to using smartphones all the time. Smartphone usage in children has both negative and positive impacts. The objective of this paper is to better understand the impact of smartphone usage on preschool and school-age children's intelligence. Methods – This paper takes a review method by 11 articles related to the main objective. Results – A resume by 11 articles reveals that damage to brain tissue and bone marrow of children’s heads absorbs almost ten times more than adults. Beyond their negative impact, still, positive impact refers to learning through interesting media so that it is easier for children to understand things they want to know. Discuss – Excessive smartphone usage by preschool children will cause various developmental problems and will cause a decrease in cognitive abilities. Excessive smartphone usage by school-age children makes children not interested in learning anymore and harms children’s achievement levels. The positive impacts are smartphone has so many educational media and applications and children can look for unlimited information easier. Conclusion – Although smartphone usage is known to have so many impacts on children’s cognitive development and children’s development in general, there is no evidence that smartphone usage has an effect on children’s intelligence which can be measured through IQ, so further research is needed.  Keywords: smartphone usage, preschool, school.